PENGARUH BOOK TAX DIFFERENCES, ARUS KAS OPERASI, TINGKAT HUTANG, DAN UKURAN PERUSAHAAN TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2011 - 2013) - Nurul Septavita; Azwir Nasir; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of book tax differences, operating cash flow, the level of debt, and firm size on earnings persistence. Independent variables used in this study are permanent differences and temporary differences which are proxy of book tax differences operating cash flow, the level of debt, and firm size, while the dependent variable in this study is the earnings persistence. Populations used in this study is manufacture companies listed on IDX 2011-2013, where the total population is used by 19 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 57 (19x3). Data analysis conducted with multiple regression model with help of software SPSS version 20,0. Of the result of the testing that has been done, the partial regression test (t test) showed that the independent variables temporary differences, operating cash flow, the level of debt, and firm size which has a significant influence on earnings persistence, while the permanent differences variables did not significantly affect the earnings persistence.Keywords : Book Tax Differences, Operating Cash Flow, Level Debt, Firm Size, and Earnings persistence